Dental applications of induced pluripotent stem cells and their derivatives. (November 2022) - Gao, Pan; Liu, Shan; Wang, Xiaoyi; Ikeya, Makoto
Abstract: Periodontal tissue regeneration is the ideal tactic for treating periodontitis. Tooth regeneration is the potential strategy to restore the lost teeth. With infinite self-renewal, broad differentiation potential, and less ethical issues than embryonic stem cells, induced pluripotent stem cells (iPSCs) are promising cell resource for periodontal and tooth regeneration. This review summarized the optimized technologies of generating iPSC lines and application of iPSC derivatives, which reduce the risk of tumorigenicity. Given that iPSCs may have epigenetic memory from the donor tissue and tend to differentiate into lineages along with the donor cells, iPSCs derived from dental tissues may benefit for personalized dental application. Neural crest cells (NCCs) and mesenchymal stem or stomal cells (MSCs) are lineage-specific progenitor cells derived from iPSCs and can differentiate into multilineage cell types. This review introduced the updated technologies of inducing iPSC-derived NCCs and iPSC-derived MSCs and their application in periodontal and tooth regeneration. Given the complexity of periodontal tissues and teeth, it is crucial to elucidate the integrated mechanisms of all constitutive cells and the spatio-temporal interactions among them to generate structural periodontal tissues and functional teeth. Thus, more sophisticated studies in vitro and in vivo and even preclinical investigations need to be conducted.